Genetic estimation of the toxic shock syndrome genes for burn patients in Al-Qadisiyah Province - Ahmed Madboub Tahir; Rana Saleh Al-Tawil ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2025)
Staphylococcus aureus is a commensal and opportunistic bacterium and the leading cause of human bacterial infections worldwide. S. aureus exhibits significant resistance to antibiotics, particularly methicillin-resistant Staphylococcus aureus (MRSA) strains. This resistance is a growing global concern, as S. aureus can rapidly adapt to various antibiotic treatments, making these bacteria difficult to treat. The ability to form biofilms enhances this resistance, allowing S. aureus to persist in infections and become resistant to antibiotics. Therefore, alternative treatment options to antibiotics are needed to control antibiotic resistance and biofilm formation, and cold plasma may be an alternative. The aim was to study genetic estimation of the toxic shock syndrome genes for burn patients in Al-Qadisiyah Province. 150 clinical samples were collected from various sources, including burns from patients aged 3–58 years at Al-Diwaniyah Teaching Hospital, Afak General Hospital, and the Specialized Burns Center during the period from February 2025 to May 2025. The results demonstrated the clear effectiveness estimation of the toxic shock syndrome genes for burn patients in Al-Qadisiyah Province.DOI: https://doi.org/10.54633/2333-024-056-005